2020
DOI: 10.3390/nu12082447
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Multivitamin and Mineral Supplement on Immune Function in Healthy Older Adults: A Double-Blind, Randomized, Controlled Trial

Abstract: Older adults are at increased risk for vitamin and mineral deficiencies that contribute to age-related immune system decline. Several lines of evidence suggest that taking a multi-vitamin and mineral supplement (MVM) could improve immune function in individuals 55 and older. To test this hypothesis, we provided healthy older adults with either an MVM supplement formulated to improve immune function (Redoxon® VI, Singapore) or an identical, inactive placebo control to take daily for 12 weeks. Prior to and after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 60 publications
0
26
0
2
Order By: Relevance
“…255,272,274,275 By this means, micronutrient insufficiencies have been identified as an international public health concern. 258,276,277 A recent study by Darnton-Hill reported that selenium, iron, potassium, sodium, calcium, magnesium, folic acid, copper, and zinc play an important role in improving the immune physiology and patient recovers earlier and decrease hospital stay among COVID-19 patients. 258 In support of that, several studies across the world advocated the importance of a balanced diet with relevant nutrients and trace elements as an extenuation approach to build robust immune physiology to fight back the COVID-19 pandemic.…”
Section: Role Of Micronutrients Vitamins and Other Trace Elements Imentioning
confidence: 99%
“…255,272,274,275 By this means, micronutrient insufficiencies have been identified as an international public health concern. 258,276,277 A recent study by Darnton-Hill reported that selenium, iron, potassium, sodium, calcium, magnesium, folic acid, copper, and zinc play an important role in improving the immune physiology and patient recovers earlier and decrease hospital stay among COVID-19 patients. 258 In support of that, several studies across the world advocated the importance of a balanced diet with relevant nutrients and trace elements as an extenuation approach to build robust immune physiology to fight back the COVID-19 pandemic.…”
Section: Role Of Micronutrients Vitamins and Other Trace Elements Imentioning
confidence: 99%
“…in a 3-month clinical trial of a MVMS containing eight vitamins and 5 minerals in older adults in Shanghai, China, Ren et al (2019) found the only status of zinc and vitamins B1, B12 and folate improved. A 12-wk randomized, placebo-controlled trial of a MVMS reported increases in the status of vitamin C and zinc but not vitamin D in healthy older adults (Fantacone et al 2020). The absence of change in the status of many of the nutrients formulated in an MVMS may be due to a variety of factors, including the nutrient dose, study duration, bioavailability, shallow doseresponse curve with adequacy or saturation at baseline, and, for minerals, limitations associated with plasma concentrations as a biomarker of whole body status (Wallace et al 2019).…”
Section: Mvms (N ¼ 35)mentioning
confidence: 98%
“…However, it is worthwhile considering the potential for these changes to increase the resilience against the risk of future untoward changes in their dietary intakes, nutrient status or health condition. Of direct relevance here is the demonstration of decreases in the length and severity of upper respiratory illnesses in a clinical trial of MVMS in healthy older adults presenting at baseline with normal ranges of vitamin and mineral status (Fantacone et al 2020). Drug treatments for cardiometabolic and gastrointestinal conditions are not curative and the potential for these and other new stresses, including the prescription of additional drugs, could precipitate micronutrient inadequacy or deficiency.…”
Section: Mvms (N ¼ 35)mentioning
confidence: 98%
“…While there is limited data in Switzerland, it appears that dietary intake is low for vitamin C, vitamin D, iron, selenium, zinc, and n-3 PUFAs, as compared to D-A-CH nutritional recommendations. This is particularly concerning for the vulnerable elderly population, for which inadequate intakes have been reported in several studies [129,130]. The risk of micronutrient deficiencies is increased in older adults due to alterations of the gastro-intestinal tract which reduces the absorption capacity, as well as changes in nutritional habits [131,132].…”
Section: Summary Of Micronutrients At Risk In the Swiss Population And Recommendationsmentioning
confidence: 99%